Atividades docentes de uma professora de matemática: artefatos mediadores na EAD - Jorge Luis Costa (2016)
Distance Learning Education (DLE) is playing an important role in the Brazilian scenery of teacher education. The Brazilian federal public universities, through the Universidade Aberta do Brasil (UAB) system, have actively participated in this educational framework. Within this context, this study aimed at understanding the relationship between the teaching activity of a mathematics teacher of a distance learning education course, which is part of the UAB system, and the mediating artifacts used and appropriate (??) by her. During this process, we tried to identify possible modifications in both the teacher's activity and the artifacts. The research questions were: (a) "How does a mathematics teacher, of a distance learning course in mathematics, use and appropriate the DLE mediating artifacts?"; (b) "How does this appropriation process can modify the teachers teaching practice and the artifacts themselves?". The research, which had a qualitative approach, adopted a perspective of Activity Theory in the organization and analysis of the data. Its focus was the Vector Algebra course taught in an undergraduate course in mathematics throught the distance learning education mode, of a Brazilian Federal University associated to the UAB system. The data were constructed on the basis of the two offerings of the referred course, one taking place in 2013/2 (2nd semester) and the other in 2015/1 (1st semester). In 2015/1, the current author acted also as a teacher-collaborator. Untill 2009, the researched teacher dedicated herself exclusively to the face-to-face teaching mode in primary and secondary education and, suddenly, she became a lecturer of a distance learning education undergraduate course. According to our observations, she is a pure mathematics lecturer who presents the course contents in an algebraic approach, using the mathematics itself as the framework for explanation and application, emphasizing the concepts and mathematical demonstrations. In her teaching practice she did not use digital technologies neither was sympathetic to their use in the process of teaching and learning. Moreover, she has not undergone any institutional training process to work in distance learning education, neither had access to a multidisciplinary team prepared to work with mathematics content in a DLE mode. Yet in her academic unit, this teacher is recognized as the one who uses the widest range of artifacts in her courses and she does it autonomously. The analysis of the data indicated that her process of artifacts appropriation may have occurred by gradual adaptations of the teaching resources she had already used in face-to-face mode, motivated by internal or external tensions in her activities. For the 2015/1 offering, the identification of these tensions also motivated her to seek new artifacts and new ways of relating herself with the elements that compose her activity, approaching the way her course was taught to what is expected for a distance learning mode.